2020
DOI: 10.1016/j.eururo.2020.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment for Recurrent Bulbar Urethral Stricture: A Randomised Open-label Superiority Trial of Open Urethroplasty Versus Endoscopic Urethrotomy (the OPEN Trial)

Abstract: This document may differ from the final, published version of the research and has been made available online in accordance with publisher policies. To read and/or cite from the published version of the research, please visit the publisher's website (a subscription may be required.) TitleSurgical treatment for recurrent bulbar urethral stricture: A randomised open label superiority trial of open urethroplasty versus endoscopic urethrotomy (The OPEN Trial).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 17 publications
5
37
0
Order By: Relevance
“…36,37 This concept has recently been challenged by the OPEN trial, the first randomised controlled trial comparing endoscopic intervention with urethroplasty for recurrent bulbar urethral strictures. 38 This trial has shown both interventions have comparable short-term outcomes, in terms of symptom control, however as expected, patients undergoing urethroplasty had a lower re-intervention rate over two years (16 v. 28%). These rates of re-intervention over the short period of follow-up in this trial, and the relatively high cost of urethroplasty meant that, at least in the UK, urethroplasty had only a 14% chance of being cost-effective for the treatment of recurrent bulbar strictures by comparison with DVIU.…”
Section: Resultssupporting
confidence: 52%
“…36,37 This concept has recently been challenged by the OPEN trial, the first randomised controlled trial comparing endoscopic intervention with urethroplasty for recurrent bulbar urethral strictures. 38 This trial has shown both interventions have comparable short-term outcomes, in terms of symptom control, however as expected, patients undergoing urethroplasty had a lower re-intervention rate over two years (16 v. 28%). These rates of re-intervention over the short period of follow-up in this trial, and the relatively high cost of urethroplasty meant that, at least in the UK, urethroplasty had only a 14% chance of being cost-effective for the treatment of recurrent bulbar strictures by comparison with DVIU.…”
Section: Resultssupporting
confidence: 52%
“…The algorithm allocated participants to each intervention in a 1:1 ratio with recruitment site and time since last procedure (< 12 months or ≥ 12 months) as minimisation covariates. Trial procedures and statistical analysis are described elsewhere [6,9]. The OPEN trial's economic analysis comprised a within trial cost-effectiveness analysis and Markov model with a 10-year time horizon.…”
Section: Methodsmentioning
confidence: 99%
“…QALYs were based on responses to the EQ-5D-5L collected at baseline, immediately prior to surgery, 1 week after catheter removal, 3,6,9,12,24 months following surgery, 18 and 24 months after randomisation and at the end of study. The responses to the EQ-5D-5L questionnaire were scored using UK population tariffs [19] to produce a health state utility score for each participant in each of the treatment groups using the area under the curve (AUC) method [20].…”
Section: Quality-adjusted Life Yearsmentioning
confidence: 99%
See 2 more Smart Citations